Changes in Corporate Social Responsibility Efficiency in Chinese Food Industry Brought by COVID-19 Pandemic—A Study With the Super-Efficiency DEA-Malmquist-Tobit Model - Chen, Zhiting; Zhu, Wenzhong; Feng, Hainuo; Luo, Houwei (Frontiers in Public Health, 2022)
Coronavirus disease 2019 (COVID-19) has brought about a significant and far-reaching impact on the world's business environment, corporations, and individuals. In the face of the general shortage of funds caused by the pandemic, assuming corporate social responsibility (CSR) is a problem for every enterprise manager. In the recent years, as corporate social responsibility (CSR) has become a hot topic globally, many enterprises have chosen to incorporate social responsibility into their development strategies. The food industry is a basic industry related to people's livelihood, especially in the pandemic. Its social responsibility efficiency deserves our attention. This article takes 17 sample enterprises whose CSR performance between 2012 and 2020 in China and reports are above the industry level as examples. Constructing the super-efficiency data envelopment analysis (DEA)-Malmquist-Tobit model explores the social responsibility efficiency of these enterprises. It analyzes the pandemic's impact on CSR efficiency. The results show that COVID-19 has promoted the social responsibility efficiency of the sample enterprises in the food industry. Besides, the level of technical efficiency and technological progress in the food industry is relatively high. Still, most enterprises are below the industry's average level. Before the outbreak of the pandemic, the size of enterprises is the key factor affecting the efficiency of CSR. After then, the listing years of enterprises then become the key factor.